Analisis Sebaran Emisi Pembangkit Listrik Tenaga Mesin Gas di Kota Batam Menggunakan Software Aermod - Riko Ferdinand Abdillah; Yayok Suryo Purnomo (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Currently, the government is increasingly building PLTMG to fulfill the electricity needs of the society. Beside for fulfill the electricity needs of the Indonesian people, PLTMG also has a negative impact on the society, especially for the community around the PLTMG in the city of Batam. So companies need to conduct studies on environmental impacts, one of which is the impact of the air produced on the surrounding area. The PLTMG industry does not use air pollution control devices, but uses a leanox combustion control system on each gas engine with a chimney outlet that emits SO2 and particulate emissions. The model simulation was carried out using Aermod view software with meteorological data from the affected locations. The results of AERMOD modeling show that the PLTMG industry will have an impact on particulate emissions in the ambient air around the activity location which will spread to the northwest, north, south and east of the activity location. The Aermod Model also shows that current conditions have resulted in dispersion with concentrations below the maximum limit stated in the 2021 Government Regulation. The addition of an emission monitoring system such as CEMS can be used to help monitor the concentration of dispersed emissions. Apart from that, emission control devices such as incinerators or combustion can also be used to reduce the concentration of the emissions used.